Microstructure and mechanical properties of laser weld of selective laser melted IN625 superalloy - Mojtaba Ghaffari Talei; Majid Ghoreishi (Journal of Materials Research and Technology)
This study investigates the microstructural evolution and mechanical properties of IN625 alloy processed by selective laser melting (SLM) and subsequently welded using laser welding. The SLM-processed base metal exhibited a columnar microstructure with preferential growth along the build direction, while the weld metal displayed a combination of cellular and columnar substructures, influenced by the heat transfer direction and solidification conditions. The equiaxed grain fraction in the weld metal increased with higher heat input, resulting in improved mechanical properties. EBSD analysis revealed significant differences in grain morphology between the base metal and weld metal, showing a higher fraction of low-angle grain boundaries (LAGB) in the weld metal due to remelting and solidification effects. Additionally, the microhardness results indicated that specimens with a uniform equiaxed microstructure exhibited the highest hardness values, whereas specimens with incomplete penetration and heterogeneous grains showed reduced hardness. Tensile test results confirmed that the highest tensile strength was observed in samples with a dominant equiaxed microstructure, due to better stress distribution and reduced stress concentration at grain boundaries. Fractographic analysis further demonstrated the influence of grain morphology on fracture behavior. Optimally welded samples exhibited ductile fracture characteristics with microscopic dimple structures, whereas samples with incomplete penetration and solidification cracks showed brittle fracture patterns. These findings highlight the critical role of laser process parameters in controlling microstructure and mechanical performance in laser-welded IN625 components, emphasizing the importance of optimizing heat input to achieve desirable mechanical properties.